2005
DOI: 10.1634/theoncologist.10-10-833
|View full text |Cite
|
Sign up to set email alerts
|

Using Single-Agent Therapy in Adult Patients with Advanced Soft Tissue Sarcoma Can Still Be Considered Standard Care

Abstract: Learning ObjectivesAfter completing this course, the reader will be able to:1. Discuss the current status of the chemotherapeutic treatment of advanced soft tissue sarcomas in adult patients.2. Explain the pitfalls in trial design when reading published papers on performed clinical studies.3. Discuss the importance of identifying the several subtypes comprising the group of soft tissue sarcomas. AbstractThe group of soft tissue sarcomas in adult patients is a heterogeneous group with more than 40 different su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 49 publications
(79 reference statements)
0
41
0
Order By: Relevance
“…With the exceptions of rhabdomyosarcomas and soft part Ewing sarcomas, systemic chemotherapy for the different STS subtypes is based on doxorubicin and ifosfamide, which remain the cornerstone first-line treatment in 2010. 10,11 In recent years, however, the insight has emerged that systemic therapy should become more tailored, and particularly for STS, according to histologic subtype. This approach is illustrated clearly by the relevant activity of imatinib in advanced dermatofibrosarcoma protuberans, 12,13 paclitaxel in angiosarcoma, 14,15 gemcitabine in leiomyosarcomas, 16,17 trabectedin in patients with myxoid/round cell liposarcomas, 18 and of mammalian target of rapamycin inhibitors in perivascular epithelioid cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…With the exceptions of rhabdomyosarcomas and soft part Ewing sarcomas, systemic chemotherapy for the different STS subtypes is based on doxorubicin and ifosfamide, which remain the cornerstone first-line treatment in 2010. 10,11 In recent years, however, the insight has emerged that systemic therapy should become more tailored, and particularly for STS, according to histologic subtype. This approach is illustrated clearly by the relevant activity of imatinib in advanced dermatofibrosarcoma protuberans, 12,13 paclitaxel in angiosarcoma, 14,15 gemcitabine in leiomyosarcomas, 16,17 trabectedin in patients with myxoid/round cell liposarcomas, 18 and of mammalian target of rapamycin inhibitors in perivascular epithelioid cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative chemotherapy is considered the only therapeutic option for patients with advanced STS which not amenable to surgery or radiotherapy (Clark et al, 2005). Doxorubicin remains the best single agent with proven activity, providing a response rate of 15%-35% in metastatic soft tissue sarcoma whatever the histological subtypes (Sleijfer et al, 2005). In EORTC 61012 trial, with 455 locally advanced STS, after a median follow-up of 56 months ,Professor Graaf concluded that doxorubicin/ ifosfamide compared with doxorubicin alone was associated with no significant difference in overall survival (OS) but with a longer PFS (median: 7.4 m versus 4.6 m; HR 0.74; 95% CI: 0.60-0.90, p=0.003) and higher overall DOI:http://dx.doi.org/10.7314/APJCP.2013.14.12…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy given with palliative intent is the only available treatment option for many patients with locally advanced unresectable and metastatic STS, yet the results are generally unsatisfactory, few patients experiencing long-term survival (Mocellin et al, 2006). Doxorubicin, first reported to have activity in sarcomas 40 years ago, remains an important first-line treatment of choice for many subtypes, Single -agent doxorubicin is the most widely accepted treatment option for these tumors (Sleijfer et al, 2005). Advanced and metastatic STSs are currently treated by doxorubicin and / or ifosfamidebased regimens at first line ,with an objective response (OR) of 23% to 48% (Maurel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A dose-response relationship for doxorubicin has been described, and it is therefore commonly recommended that doxorubicin be administered at doses between 70 mg/m 2 and 80 mg/m 2 in 3-week intervals [7,8]. The use of doxorubicin is mainly limited by myelosuppression and cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%